Krukenberg's Tumor - Huaraz, David (1997)
We report the case of a 37-years-old woman, who was treated for a metastatic carcinoma located at the ovary from extragenital source: Krukenberg´s tumor, at the Surgery Department N.º 5, Hospital Nacional Guillermo Almenara Irigoyen - IPSS. The tumor showed signet ring cells in cellular stroma, derivated from ovarian stroma. The primary neoplasm was gastric cancer and has been submitted to total gastrectomy plus omentectomy (R-II Resection) with esophagus-jejuno lateral end anastomosis in Y of Roux with autosuture.After 18 months, she underwents a second intervention: total abdominal hysterectomy and bilateral salpinx oophorectomy, showing ascitis and bilateral enlarged solid ovarian masses. Her survival was 24 months after the first intervention.